Light signal sending and receiving using Si light‐emitting diode. Issue 3 (15th February 2013) - Kawakami, Yohei; Okamoto, Kensho
Abstract It has been thought that silicon (Si) is a material inapplicable to active optical devices such as light‐emitting diodes (LED) because of its indirect electronic band structure. However, one of the present authors (Okamoto) discovered that commercially available Si photodiodes emitted infrared light, and he developed an original and unique two‐way optical communication system in which each Si photodiode (Si‐PD) played the two roles of light‐emitting diode and light receiver. In this study, we report the observation directly infrared light emission from a PN Si‐PD and a PIN Si‐PD using an infrared camera and measurement of the emission spectra of the Si‐PDs. We succeeded in sending and receiving light signals at room temperature between two PN Si‐PDs, between two PIN Si‐PDs, and also between an Si‐PD and an InGaAs photodiode. This paper presents our novel system for sending and receiving light signals using an Si‐PD as a LED. © 2013 Wiley Periodicals, Inc. Electron Comm Jpn, 96(3): 38–44, 2013; Published online in Wiley Online Library (wileyonlinelibrary.com). DOI 10.1002/ecj.11410